2012
DOI: 10.1098/rsif.2011.0854
|View full text |Cite
|
Sign up to set email alerts
|

The well-tuned blues: the role of structural colours as optical signals in the species recognition of a local butterfly fauna (Lepidoptera: Lycaenidae: Polyommatinae)

Abstract: The photonic nanoarchitectures responsible for the blue colour of the males of nine polyommatine butterfly species living in the same site were investigated structurally by electron microscopy and spectrally by reflectance spectroscopy. Optical characterization was carried out on 110 exemplars. The structural data extracted by dedicated software and the spectral data extracted by standard software were inputted into an artificial neural network software to test the specificity of the structural and optical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 38 publications
3
87
0
2
Order By: Relevance
“…Our recent investigations showed that in the case of nine closely related blue Polyommatus butterfly species the spectral sensitivity of their eyes (sensor) and the dorsal structural coloration of the wings (measured object) are well tuned for safe mate / competitor recognition [11]. Based on our noninvasive spectral measurements [12] on numerous museum exemplars, we showed that the dorsal coloration is species specific and stable in time.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Our recent investigations showed that in the case of nine closely related blue Polyommatus butterfly species the spectral sensitivity of their eyes (sensor) and the dorsal structural coloration of the wings (measured object) are well tuned for safe mate / competitor recognition [11]. Based on our noninvasive spectral measurements [12] on numerous museum exemplars, we showed that the dorsal coloration is species specific and stable in time.…”
Section: Introductionmentioning
confidence: 83%
“…To evaluate the vapor sensing data we used the color representation of the Polyommatine butterflies based on the CIE tristimulus color matching [11,19]. This tridimensional color space was created using the sensitivity functions of the four photoreceptors occurring in the eyes of the Lycaenid butterflies [13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations